THE ROLE OF HALAL-FRIENDLY HOSPITALITY SERVICES IN INCREASING VISIT INTENTION: A MUSLIM TOURIST PERSPECTIVE (International Journal of Islamic Business, 2023)
Halal friendly hospitality, rooted in the Quran and Hadith, signifies the practice of providing guests with Halal-compliant food, beverages, and accommodations. This study investigates the pivotal role of Halal friendly hospitality services in enhancing visit intention among Malaysian Muslim tourists. It delves into the influence of push and pull factors on this intent. The study employed a proposed model, utilizing survey data collected from 300 local Muslim tourists in Malaysia. The results unequivocally reveal a positive and significant correlation between push and pull factors and Halal friendly hospitality services with overall satisfaction. Furthermore, it highlights a substantial connection between overall satisfaction and the intention to revisit. Significantly, the study contributes to the understanding of how overall satisfaction acts as a mediator between Halal friendly hospitality, push and pull factors, and revisit intention, shedding light on the practical implications for the hospitality industry. This study's findings offer valuable insights for the hospitality industry, emphasizing the significance of Halal friendly hospitality services in attracting and retaining Malaysian Muslim tourists. Understanding the mediating role of overall satisfaction can assist hospitality providers in tailoring their services to enhance the revisit intention of this demographic, ultimately contributing to sustainable growth in the sector.